Biology and clinical utilization of mesenchymal progenitor cells - Minguell,J.J. (2000)
Within the complex cellular arrangement found in the bone marrow stroma there exists a subset of nonhematopoietic cells referred to as mesenchymal progenitor cells (MPC). These cells can be expanded ex vivo and induced, either in vitro or in vivo, to terminally differentiate into at least seven types of cells: osteocytes, chondrocytes, adipocytes, tenocytes, myotubes, astrocytes and hematopoietic-supporting stroma. This broad multipotentiality, the feasibility to obtain MPC from bone marrow, cord and peripheral blood and their transplantability support the impact that the use of MPC will have in clinical settings. However, a number of fundamental questions about the cellular and molecular biology of MPC still need to be resolved before these cells can be used for safe and effective cell and gene therapies intended to replace, repair or enhance the physiological function of the mesenchymal and/or hematopoietic systems.